2002
DOI: 10.1017/s0016756802006945
|View full text |Cite
|
Sign up to set email alerts
|

Whole-rock geochemical variations and evolution of the arc-derived Murihiku Terrane, New Zealand

Abstract: Arc-flank volcaniclastic sedimentation in the Murihiku Terrane of New Zealand lasted about 120 million years from Late Permian to Early Cretaceous time. Despite the effects of pervasive zeolite-facies alteration, whole-rock geochemical parameters for sandstones, siltstones and tuffs record changes in source-rock composition, both in time and along the length of the depositional basin. Sandstones are considered to give a more reliable indication of the state of evolution of the source volcanic arc than do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 39 publications
1
51
1
Order By: Relevance
“…Thus, the ratio Q/(F + Q) is mostly less than about 10%, although it rises to 30% or more in Pilot Point Sandstone and Short Bay Formation. Relatively low SiO 2 contents of sandstones at the base of the Bates and in the Potiki (Table 1) match those of early Etalian and pre-Etalian age in the Murihiku Supergroup Southland Syncline (Roser et al 2000) and result from substantial basaltic andesite to andesitic contributions. Increased felsic volcanism is recorded in later Etalian and Kaihikuan Murihiku rocks with an incoming of significant granitoid detritus (Roser et al 2002).…”
Section: Volcanism and Geochemistrymentioning
confidence: 69%
See 1 more Smart Citation
“…Thus, the ratio Q/(F + Q) is mostly less than about 10%, although it rises to 30% or more in Pilot Point Sandstone and Short Bay Formation. Relatively low SiO 2 contents of sandstones at the base of the Bates and in the Potiki (Table 1) match those of early Etalian and pre-Etalian age in the Murihiku Supergroup Southland Syncline (Roser et al 2000) and result from substantial basaltic andesite to andesitic contributions. Increased felsic volcanism is recorded in later Etalian and Kaihikuan Murihiku rocks with an incoming of significant granitoid detritus (Roser et al 2002).…”
Section: Volcanism and Geochemistrymentioning
confidence: 69%
“…Relatively low SiO 2 contents of sandstones at the base of the Bates and in the Potiki (Table 1) match those of early Etalian and pre-Etalian age in the Murihiku Supergroup Southland Syncline (Roser et al 2000) and result from substantial basaltic andesite to andesitic contributions. Increased felsic volcanism is recorded in later Etalian and Kaihikuan Murihiku rocks with an incoming of significant granitoid detritus (Roser et al 2002). Kaka Point Volcanic Sandstone and Pilot Point Sandstone are also notably SiO 2 -rich, but highly felsic sandstones from SE Willsher Bay Karoro Formation (Table 1) evidently had a different source from Southland Syncline rocks of the pre-Etalian age established for part of Karoro Formation.…”
Section: Volcanism and Geochemistrymentioning
confidence: 69%
“…Prame and Pohl 1994;Slack and Stevens 1994;Dabard et al 1996;Garzione et al 1997;Roser et al 2002). Condie and Wronkiewicz (1990) concluded that the Cr/Th ratio in pelites can provide an important geochemical index of early Precambrian crustal evolution and can be used to monitor changes in source composition with strong correlations to Th/Sc, Sc/Th and La/Sc ratios.…”
Section: Regional Chemostratigraphymentioning
confidence: 99%
“…For purposes of petrographic and geochemical description, and to track variations in composition with time, the rocks of the Murihiku Terrane in the North Island have been subdivided into four stratigraphic provenance groups, or age bands, using the format of New Zealand stage names and symbols ( These age bands are similar to those used by Roser et al (2002), except their stratigraphic provenance groups extend back to the Late Permian for the Southland sequence, and their Late Triassic age band extends from the Kaihikuan (early Late Triassic) to the Warepan. Emphasis is placed in this paper on the petrography of the sandstones which are classified as feldspathic arenites and lithic arenites (Boggs 2001), and are texturally and mineralogically immature.…”
Section: Petrographymentioning
confidence: 99%
“…Trace elements are particularly useful in this regard, especially those that are relatively immobile like La, Y, Th, Zr, Hf, Nb, Ti, and Sc. These elements behave geochemically with relatively low mobility during sedimentary processes of weathering, transportation, and burial (McLennan et al 1983), and also during diagenetic and very low grade metamorphic reconstitution (Roser et al 2002). Hence, the abundances of immobile trace elements in the sandstones can be used as reliable signatures inherited from the parent material, and sandstones are more reliable than siltstones or mudstones as they contain less matrix and more detrital components, and represent near-source deposition (Roser et al 2002).…”
Section: Geochemistrymentioning
confidence: 99%